Leishmania donovani Targets Dicer1 to Downregulate miR-122, Lower Serum Cholesterol, and Facilitate Murine Liver Infection - Ghosh, June (Cell Press, 2013)
Leishmania donovani causes visceral leishmaniasis (VL) where the parasite infects and resides inside liver and spleen tissue macrophages. Given the abnormal lipid profile observed in VL patients, we examined the status of serum lipids in an experimental murine model of VL. The murine VL liver displayed altered expression of lipid metabolic genes, many of which are direct or indirect targets of the liver-specific microRNA-122. Concomitant reduction of miR-122 expression was observed in VL liver. High serum cholesterol caused resistance to L. donovani infection, while downregulation of miR-122 is coupled with low serum cholesterol in VL mice. Exosomes secreted by the infective parasites caused reduction in miR-122 activity in hepatic cells. Leishmania surface glycoprotein gp63, a Zn-metalloprotease, targets pre-miRNA processor Dicer1 to prevent miRNP formation in L. donovani-interacting hepatic cells. Conversely, restoration of miR-122 or Dicer1 levels in VL mouse liver increased serum cholesterol and reduced liver parasite burden.